Spontaneous pneumothorax secondary to chronic cavitary pulmonary histoplasmosis - Samuel Geurkink; Leslie Cler (Greater Baltimore Medical Center, 2020)
Histoplasma capsulatum is a dimorphic fungus that causes histoplasmosis. Chronic cavitary pulmonary histoplasmosis is rare, and typically manifests as apical cavitary lesions in patients with pre-existing chronic obstructive pulmonary disease. We report a case involving a 60-year-old female who presented to our facility with acute onset of dyspnea and dry cough. Chest x-ray revealed a large left-sided pneumothorax with nearly complete collapse of the left lung. A chest computed tomography scan revealed a left upper lobe cavitary lesion with a bronchopleural fistula. After thoracic surgical bleb resection, a surgical specimen sent for biopsy was positive for Histoplasma capsulatum. The patient's pneumothorax was subsequently diagnosed as chronic cavitary pulmonary histoplasmosis, and itraconazole treatment was initiated. After admission, the patient underwent a thoracotomy with decortication to improve lung expansion; however, the patient's pneumothorax persisted. After a prolonged hospital stay and serial chest x-rays that showed stable residual pneumothorax, the patient was discharged to a long-term acute care facility and itraconazole treatment was continued. Two months after discharge, a repeat chest x-ray showed resolution of her left-sided pneumothorax. This case report highlights the importance of considering pulmonary histoplasmosis (or other endemic pulmonary fungal infections) when a patient presents with apical cavitary lesions.